Santiago Ramón y Cajal, 85 Years since his Death. Comments on his Latest Literary Work - Salvador Salvador, Julio (Razón y fe, 2020)
October 2019 marks the eighty-fifth anniversary of the death of Santiago Ramón y Cajal, Nobel Prize for Medicine of 1906. That same year, 1934, El mundo visto a los ochenta años. Impresiones de un arteriosclerótico, his last work, was published. This collection of essays, halfway between memories and miscellaneous, reflects all kinds of social, cultural and scientific issues, seen through Cajal’s awareness of his old age. This work stands out for the different literary references that are observed. Also, a chapter is dedicated to the phenomenon of secessionism in Spain.